Attitude of stakeholders toward monitoring and evaluation of students' research projects in tertiary education inOyo state, Nigeria (2013)
This study investigated stakeholders' perception of monitoring and evaluation of students' research projects in some tertiary educational institutions in Oyo state. The population of the studycomprised all the tertiary institution in Oyo state. Multistage sampling technique was adopted as follows: Random sampling technique was used to select one university and one college of education after classifying the institutions into universities and non- universities. From each of the institution, two faculties/schools were randomly selected while six departments were randomly chosen from each of the faculty/school. The had of department , 4 lecturers and 5 students were purposively selected from each department, making a total of 24 HODs, 96 lecturess and 120 Ph. D students. Monitoring and Evaluation of Research Projects Scale (MERPS) and Students' Perception of Lectures Attitude towards Monitoring and Evalaution of Research Project Scale(SPLAMERPS) were employed to generate data. Cronbach alph was used to determine the psychometric properties of these instruments validity coefficients were 0.76 and 0.79 repectively. Three research questions were addressed. Descriptive statistic were used to anlayze the data. Results revealed that all the HODs, 48% of the lecturers accepted M & E of students' research projects as a tool for quality assurance mechanism, while 52% of lecturers opposed it. Recommendations were that: lecturers should be made to imbibe the M & E mechanism to effectively and efficiently montior and evaluate students' research projects/theses. Lecturers should adhere strictly the benchmark set for monitoring and evaluationof students' project to ensure good quality.